Understanding virtual reality challenging perspectives for media literacy and education - McDougall, Julian; Dawkins, Steve (Writer on media studies); Jones, Sarah (Writer on virtual reality) (Abingdon, Oxon New York, NY Routledge, 2023)
"This book provides critical commentary on key issues around virtual reality, using media technology as a tool to challenge perspectives for learning and understanding cultural diversities. With a focus on empathy, embodiment and ethics, the book interrogates the use of immersive technologies for formal and informal educational contexts. Taking a critical approach to discourses around emerging technology and learning, the book presents the idea that a new literacy is emerging and an emphasis on media and technology is needed in the context of education to explore and experience cultural diversities. Employing a personal reflexive narrative, the chapters highlight key issues through research and interviews with leading practitioners in the field. Understanding Virtual Reality will be of great interest to academics and students interested in the effects of immersive realities on the education experience, and to anyone keen on exploring the paradigm shift from entertainment to education"--
Understanding VR audiences / Verity McIntosh -- Teaching XR : digital inequalities and education / Jenny Kidd and James Taylor -- How to use social VR in higher education : case study of JUXYR campus in Finland / Turo Uskali, Matti Rautiainen, Merja Juntunen, Riitta Tallavaara and Mikko Hiljanen.
Includes bibliographical references and index (175-181).
Keywords: Computer literacy; Media programs (Education); Virtual reality -- Study and teaching